Identification of Differentially Expressed Genes Associated with Prognosis of B Acute Lymphoblastic Leukemia - Garza Veloz, Idalia; Martínez Fierro, Margarita de la Luz; Jaime Pérez, José Carlos; Carrillo Sanchez, Karol; Ramos Del Hoyo, Maria Guadalupe; Lugo Trampe, Ángel; Rojas Martínez, Augusto; Gutiérrez Aguirre, César Homero; González Llano, Óscar; Salazar Riojas, María del Rosario; Hidalgo Miranda, Alfredo; Gómez Almaguer, David; et al. (2015)
Acute lymphoblastic leukemia type B (B-ALL) is a neoplastic disorder with high mortality rates. The aim of this study was to validate the expression profile of 45 genes associated with signaling pathways involved in leukemia and to evaluate their association with the prognosis of B-ALL. Methods. 219 samples of peripheral blood mononuclear cells obtained from 73 B-ALL patients were studied at diagnosis, four, and eight weeks after starting treatment. Gene expression was analyzed by quantitative realtime polymerase chain reaction. Results. Normalized delta Cq values of 23 genes showed differences between B-ALL and controls at diagnosis time (